The Military Doctrine of Azerbaijan: Assessing the Implementation Process and Policy Implication - Kharatyan, Tina (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
In June 2010 the Military Doctrine was adopted in Azerbaijan, and new policies were put into implementation based on the vision of the document. The MD has become the proper installation of Azerbaijani aspirations to restore territorial integrity by any means including military operations. The document provided an impetus to spend billions of dollars on purchasing weaponry, developing army structure, constructing new military bases and enlarging arms production.
Keywords: Military Science